A Study on the Functional Problems Faced by the Handloom Cooperative Societies in Tamil Nadu - Durai, F. R. Alexander Pravin (Indian Journal of Marketing, 2005)
RTextile industry plays a unique role in the economic progress of our nation. This industry contributes nearly 14% to the total industrial production and earns around Rs.52,000 crores through exports, which account for about 38% of country export earnings. Moreover, textile industry alone contributes Rs.7000 crores as duties to central exchequer. India is, in fact, a world leader in yarn production with a global share of 28%. The area under cotton cultivation is 9 million hectares, which is the largest in the world while the annual cotton production is around 3000 million kilogram. Textile industry in India consists of organized mill sector and decentralized handloom, Power loom and khadi sectors. Indian textile industry with a 58% global share of looms consisting of 3.5 million handlooms and 1.8 million power looms, 1300 spinning units and over 275 composite mills, is a force to reckon with, in the global textile arena.